Manual of devotion and instruction in the Chipewyan language for the Indians of Churchill [electronic resource] - Kirkby, W. W. (William West), 1827-1907 (London : Society for Promoting Christian Knowledge)
With syllabarium. Text in Chipewyan syllabics; captions in English. Electronic reproduction. Mode of access: Internet. 44